Graphene nanoplatelets as novel reinforcement filler in poly(lactic acid)/epoxidized palm oil green nanocomposites: mechanical properties - Chieng, Buong Woei; Ibrahim, Nor Azowa; Wan Yunus, Wan Md. Zin; Hussein, Mohd Zobir; Silverajah, V. S. Giita (MDPI, 2012)
Graphene nanoplatelet (xGnP) was investigated as a novel reinforcement filler in mechanical properties for poly(lactic acid) (PLA)/epoxidized palm oil (EPO) blend. PLA/EPO/xGnP green nanocomposites were successfully prepared by melt blending method. PLA/EPO reinforced with xGnP resulted in an increase of up to 26.5% and 60.6% in the tensile strength and elongation at break of the nanocomposites respectively, compared to PLA/EPO blend. XRD pattern showed the presence of peak around 26.5° in PLA/EPO nanocomposites which corresponds to characteristic peak of graphene nanoplatelets. However, incorporation of xGnP has no effect on the flexural strength and modulus. Impact strength of PLA/5 wt% EPO improved by 73.6% with the presence of 0.5 wt% xGnP loading. Mechanical properties of PLA were greatly improved by the addition of a small amount of graphene nanoplatelets ( < 1 wt%).